Inhibition of signal peptidase complex expression affects the development and survival of Schistosoma japonicum - Yang, Wen-Bin; Luo, Fang; Zhang, Wei; Sun, Cheng-Song; Tan, Cong; Zhou, An; Hu, Wei (Frontiers in Cellular and Infection Microbiology, 2023)
Schistosomiasis, the second most neglected tropical disease defined by the WHO, is a significant zoonotic parasitic disease infecting approximately 250 million people globally. This debilitating disease has seriously threatened public health, while only one drug, praziquantel, is used to control it. Because of this, it highlights the significance of identifying more satisfactory target genes for drug development. Protein translocation into the endoplasmic reticulum (ER) is vital to the subsequent localization of secretory and transmembrane proteins. The signal peptidase complex (SPC) is an essential component of the translocation machinery and functions to cleave the signal peptide sequence (SP) of secretory and membrane proteins entering the ER. Inhibiting the expression of SPC can lead to the abolishment or weaker cleavage of the signal peptide, and the accumulation of uncleaved protein in the ER would affect the survival of organisms. Despite the evident importance of SPC, in vivo studies exploring its function have yet to be reported in S.japonicum. The S.japonicum SPC consists of four proteins: SPC12, SPC18, SPC22 and SPC25. Our results showed that RNAi-SPC delayed the worm's normal development and was even lethal for schistosomula in vivo. The knockdown of SPC25 led to the degeneration of reproductive organs, such as the ovaries and vitellarium of female worms. Moreover, SPC25 knockdown led to the degeneration of reproductive organs and reduced egg production in the female worm while reducing the pathological damage of the eggs to the host. Additionally, SPC-related inhibitors AEBSF or suppressing the expression of SPC25 also impacted the pairing and the viability of cultured worms in vitro. Together, these data demonstrate that SPC is crucial in controlling the growth and reproduction of S. japonicum, which presents a novel viewpoint on preventing worm fecundity and maturation while searching for potential drug targets.